Romanian traditional products - Valentina Tudor; Ioana Măcău; Marian Butu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The countryside is an available and eligible resource, with an unexploited growth potential for the exploitation of which is necessary to converge efforts of policy makers both at national level and in the Member States regarding the design, implementation, monitoring and evaluation of agricultural policies. The central elements of the policy - farms and farmers - will be central elements of the Common Agricultural Policy for the period 2014-2020.
Keywords: 330; Local agriculture; farmers; traditional products; consumers; consultancy